Hydrothermal synthesis and properties of titania nanotubes doped with Fe, Ni, Zn, Cd, Mn - Kulish, M.R.; Struzhko, V.L.; Bryksa, V.P.; Murashko, A.V.; Il’in, V.G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
Fe/TiO₂, Mn/TiO₂, Zn/TiO₂, Cd/TiO₂, Ni/TiO₂ titania nanotubes were synthesized by the method of direct hydrothermal synthesis. Their properties have been investigated using X-ray phase analysis and X-ray fluorescent analysis, high-resolution transmission electron microscopy, luminescent spectroscopy and Raman scattering. It has been ascertained that the Fe/TiO₂, Mn/TiO₂, Zn/TiO₂, TiO₂ titania nanotubes possess the structure of Na₂Ti₂O₄(OH)₂. The structure of Cd/TiO₂ titania, probably, is mixture of anatase and rutile phases. We have found that Fe, Mn, Zn, Cd, Ni does not form solid solution with TiO₂, and these metals are located in interlayer space. The mechanism of nanotube formation has been briefly discussed.
Remove selected